Efektivitas Discovery Learning Materi Elektrolit-Non Elektrolit dalam Meningkatkan KPS Ditinjau dari Kemampuan Akademik - Nur Ngafifah Jamil; Ila Rosilawati; Noor Fadiawati (Universitas Lampung, 2018)
This research was aimed to describe effectiveness of discovery learning to improve science process skills on the electrolyte and nonelectrolyte topic viewed from academic ability. Method of this research is quasi experimental with factorial 2 x 2 design. The sample of this research are X IPA 3 as the experiment class and X IPA 1 as the control class that obtained by purposive sampling technique. Data analysis techniques used two ways ANOVA and descriptive analysis. The result of this research showed that: there was no interaction between discovery learning and academic ability towards students’ science process skill; discovery learning was effective to improve students’ science process skill on the electrolyte and nonelectrolyte topic; the percentage of high academic ability students with high n-gain category is greater than medium and low academic ability students on discovery learning.Penelitian ini bertujuan untuk mendeskripsikan efektivitas model discovery learning dalam meningkatkan KPS siswa pada materi larutan elektrolit dan non elektrolit ditinjau dari kemampuan akademik siswa. Metode penelitian yang digunakan adalah quasi experiment dengan desain faktorial 2 x 2. Sampel dalam penelitian ini adalah kelas X IPA3 sebagai kelas eksperimen dan kelas X IPA 1 sebagai kelas kontrol yang diperoleh melalui teknik purposive sampling. Data penelitian dianalisis menggunakan uji two ways ANOVA dan analisis deskriptif. Hasil penelitian menunjukkan bahwa: tidak terdapat interaksi antara penggunaan model discovery learning dengan kemampuan akademik terhadap KPS siswa; model discovery learning efektif untuk meningkatkan KPS siswa pada materi larutan elektrolit dan non elektrolit; pada penggunaan model discovery learning, persentase siswa kemampuan akademik tinggi dengan kategori n-gain tinggi lebih besar daripada siswa akademik sedang dan rendah.Kata kunci: discovery learning, larutan elektrolit dan non elektrolit, KPS, kemampuan akademik